2021
DOI: 10.1177/13634607211026457
|View full text |Cite
|
Sign up to set email alerts
|

I thought we were vibin’: A qualitative exploration of sexual agency and consent in young people

Abstract: While there is much attention paid to the connection between social boundaries and consent, the relationship between consent literacy and sexual agency has not yet been explored. This qualitative analysis, which is part of a larger mixed-methods study, sought to explore the relationship between consent literacy and sexual agency in young people. Participants ( n = 18) were recruited from nonprofit organizations and were asked to complete a 30–40 minutes semi-structured interview and two questionnaires. Through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…For women with strong stereotypical gender role beliefs, acquiescence to sexual advances is expected; refusal of sex is contrary to the heterosexual script (Conroy et al, 2015; Joskowski et al, 2017). Similarly, seeking sexual consent requires sexual agency and assertiveness that falls outside the heterosexual sexual script (Moore & Reynolds, 2016; Schobert et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For women with strong stereotypical gender role beliefs, acquiescence to sexual advances is expected; refusal of sex is contrary to the heterosexual script (Conroy et al, 2015; Joskowski et al, 2017). Similarly, seeking sexual consent requires sexual agency and assertiveness that falls outside the heterosexual sexual script (Moore & Reynolds, 2016; Schobert et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recent definitions also include making informed and ethical choices for themselves and accepting responsibility for those choices. Qualitative evidence showed that developing the ability to negotiate consent was seen by young people as a critical component of sexual agency (Schobert et al, 2021).…”
Section: Research Conceptualizations Of Sexual Competencementioning
confidence: 99%
“…However, female and male participants with various sexual identities and sexual experience backgrounds were included in this study to achieve diversity in the mental representation of sexual competence. LGBTQI+ individuals may differ in their understanding of sexual competence from heterosexual individuals, as suggested by a small-scale qualitative study by Schobert et al (2021). To identify differences and overlap, future research should study the understanding of sexual competence in larger samples of sexual-minority participants.…”
Section: Limitationsmentioning
confidence: 99%